Efficiency and Effectiveness of Waste Management: An Analysis from a Local Budget Policy Perspective - Samsul Arifin; Reza Aulia Prastiwi; Devi Raj Angely; Hartuti Purnaweni; Maryono Maryono (Journal La Sociale, 2026)
One of the important challenges in sustainable development goals is waste management, especially in metropolitan cities such as Semarang, which has experienced an increase in population from 1 million to 1.7 million in the last two decades. This study aims to analyze budget allocation, measure efficiency and effectiveness levels, and examine the relationship between budget allocation and waste management performance in Semarang for the period 2021–2024. The methods used are descriptive and analytical quantitative methods. This approach is used to describe the amount of budget allocation for waste management programs. Quantitative analysis is conducted through Data Envelopment Analysis (DEA) to measure efficiency and Cost Effectiveness Analysis (CEA) to measure effectiveness and the relationship between budget allocation and performance achievements. The results of the study show that the budget allocation fluctuated, with the highest in 2022 and the lowest in 2024, with the largest allocation in the sub-activity of waste management through transportation. The DEA analysis shows that 2024 is the most efficient year (score of 1.00) and 2022 is the least efficient year (score of 0.73). The CEA analysis shows that 2024 will be the most effective year with an allocation of Rp69.1 billion, a cost per ton of waste reduction of Rp575,229/ton, a cost per ton of managed waste of Rp160,747/ton, and a cost per ton of recycling of Rp587,554/ton. Pearson's correlation test shows that there is no relationship between the budget amount and performance achievements